Genetics of pediatric hearing loss: A functional perspective - Khela, Harmon (Laryngoscope Investig Otolaryngol, 2020)
OBJECTIVES: This article reviews the current role of genetics in pediatric hearing loss (HL). METHODS: A review of the current literature regarding the genetic basis of HL in children was performed. RESULTS: To date, 119 nonsyndromic genes have been associated with HL. There are also hundreds of syndromic causes that have HL as part of the clinical phenotype. CONCLUSIONS: Identifying HL genes coupled with clinical characteristics (“genotype‐phenotype”) yields a more accurate diagnosis and prognosis. Although the complexity of the auditory apparatus presents challenges, gene therapy is emerging and may be a viable management option in the future.